1999
DOI: 10.1203/00006450-199910000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Body Composition: Dual-Energy X-Ray Absorptiometry, Magnetic Resonance Imaging, and Three-Dimensional Chemical Shift Imaging versus Chemical Analysis in Piglets

Abstract: An animal study to evaluate dual-energy x-ray absorptiometry (DXA) and magnetic resonance (MR) imaging and spectroscopy for measurement of neonatal body composition was performed. Twenty-three piglets with body weights ranging from 848 to 7550 g were used. After measuring total body water, animals were killed and body composition was assessed using DXA and MR (1.5 T; MR imaging, T1-weighted sagittal spin-echo sequence; MR spectroscopy, three-dimensional chemical shift imaging) as well as chemical carcass analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 41 publications
5
37
0
Order By: Relevance
“…The discrepancy (1.0%) was similar to that reported in previous validation studies, 1.2%, 23 1.4%, 21 16 In accord with most of the other validation studies which have compared total body ash to DXA estimates of bone mineral content we found that the DXA estimate was substantially lower than the total ash estimate. Fusch et al 23 and Picaud et al 17 both found a shortfall of 42% by DXA in small piglets and Brunton et al 16 reported discrepancies of on average 30% in small pigs, but not in larger animals. Mitchell et al 21 also reported no signi®cant difference in larger animals.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The discrepancy (1.0%) was similar to that reported in previous validation studies, 1.2%, 23 1.4%, 21 16 In accord with most of the other validation studies which have compared total body ash to DXA estimates of bone mineral content we found that the DXA estimate was substantially lower than the total ash estimate. Fusch et al 23 and Picaud et al 17 both found a shortfall of 42% by DXA in small piglets and Brunton et al 16 reported discrepancies of on average 30% in small pigs, but not in larger animals. Mitchell et al 21 also reported no signi®cant difference in larger animals.…”
Section: Discussionsupporting
confidence: 75%
“…Other studies point to an important role for tissue hydration in the error in estimates of fat content by DXA. 23,30 In particular, Fusch et al 23 found that tissue hydration declined as a function of increasing body mass in their experimental subjects, and this decrease in hydration was linked to an increasing underestimate of the fat content of the animals. Although Going et al 31 manipulated hydration status and found no effect on fat content by DXA, in a sample of 19 adults, the extent of their manipulations (less than 2%) was small relative to the individual variability in tissue hydration, and in the range where our own in vitro manipulations detected no effect (Figure 3b).…”
Section: Discussionmentioning
confidence: 99%
“…Body composition was determined using a reference method, DXA, because its use in small infants was validated independently by multiple investigators (18,19,27,28). We have also shown that the measurement from pencil-beam DXA technique used in this study is highly predictive of those obtained by the newer fan-beam DXA technique (29).…”
Section: Discussionmentioning
confidence: 99%
“…DXA is acknowledged as the standard (Dezenberg et al, 1999) and most precise (Fusch et al, 1999) method to assess body fat mass. Therefore in this study it is used as the standard method comparison to BIA technique, although it can only be used in a hospital and requires the use of a very low dose of radiation (Pietrobelli et al, 1998).…”
Section: Introductionmentioning
confidence: 99%